1996
DOI: 10.1128/iai.64.6.2336-2338.1996
|View full text |Cite
|
Sign up to set email alerts
|

Influence of opsonization conditions on C3 deposition and phagocyte binding of large- and small-capsule Cryptococcus neoformans cells

Abstract: Previous studies demonstrated that, following opsonization with normal human serum (NHS), phagocytes bind greater numbers of small-capsule Cryptococcus neoformans cells than yeast cells with large capsules. The present study tested the hypothesis that suboptimal deposition of opsonic C3 fragments contributes to this disparity. C. neoformans was grown under conditions promoting large or small capsules and was incubated at various concentrations in NHS. At low concentrations of yeast cells (125 cells per l of NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Next, we considered that complement concentration was a limiting factor, as has been suggested 31. So we investigated whether media that had contained C. neoformans retained sufficient complement activity to support a second phagocytosis with fresh yeast cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we considered that complement concentration was a limiting factor, as has been suggested 31. So we investigated whether media that had contained C. neoformans retained sufficient complement activity to support a second phagocytosis with fresh yeast cells.…”
Section: Resultsmentioning
confidence: 99%
“…If this mechanism is operative, strain differences inthe response of the capsule to complement binding could contribute to inter‐strain variability. Finally, prior studies 31 strongly argue against the notion that differences in C. neoformans complement‐mediated phagocytosis are a result of differences in the degradation patterns of C3 to C3b and iC3b 29.…”
Section: Discussionmentioning
confidence: 97%
“…Several findings suggest that the efficiency of complement‐mediated phagocytosis depends on the size of the cryptococcal capsule (Zaragoza et al ., ). Early studies reported an inverse correlation between complement‐mediated phagocytosis and capsule size (Mitchell & Friedman, ; Kozel et al ., ) based on the finding that cells with large capsule bound a lower amount of C3, which suggests that cells with large capsule were less efficiently phagocytosed (Kozel et al ., ). In addition, the site of complement localization on the capsule plays an important role in determining the efficiency of phagocytosis.…”
Section: How Is C Neoformans Phagocytosed?mentioning
confidence: 99%
“…107 Fortunately, the capsule represents an extremely powerful activator of the complement cascade, achieving a deposition of up to 10 7 -10 8 C3 molecules per yeast cell while acapsular cryptococcal cells bind at least ten times less C3. [108][109][110] The predominant pathway as well as the precise localisation of opsonising C3 is species-specific; human complement induces a deposition of C3 at the outermost capsular surface, mainly via activation of the alternative pathway. 111 The localisation of C3 is of major importance for the efficacy of phagocytosis: whereas deposition inside the capsule is characteristic for poor phagocytosis, an opsonisation at the outer capsule edge allows efficient ingestion.…”
Section: Complement-mediated Effector Mechanisms In Cryptococcal Infementioning
confidence: 99%